Hybrid Modeling and Simulation for Through-the-Wall Human Detection Using IR-UWB Distributed Radar Systems - Lee, Soyeong; Yoon, Daeyeong; Hwang, Kyuhwan; An, Min; Park, Kyung Hwan; Bae Park, Yong (IEEE Sensors Journal, 2024)
We propose a hybrid modeling technique for human signal detection through the walls using distributed radar. The high resolution and excellent penetration performance of the impulse radio ultrawideband (IR-UWB) radar systems can be used in important applications such as survivor detection in disaster scenarios. The radar channel transfer function between the transmitting and receiving radars obtained from the electromagnetic (EM) simulator is used for signal processing on MATLAB, followed by coherent synthesis. We perform a hybrid simulation of human detection through the walls using a single radar and verify it through experiments. In addition, we model vital signs behind the walls in various scenarios using the distributed radar and present the coherent synthesis results. The proposed hybrid modeling technique allows us to analyze various distributed radar scenarios in advance. This can reduce the time-consuming and resource-intensive real experiments. It is expected to contribute to radar system design optimization, signal processing algorithm development, and the identification of potential errors before practical implementation. The proposed method is expected to play an important role in various applications of IR-UWB radar technology, including disaster relief operations, noncontact biosignal monitoring, security, and surveillance systems.
Keywords: Coherent distributed radar; Hybrid distributed radar modeling; Hybrid model; Hybrid simulation; Impulse Radio; Impulse radio ultra-wideband radar; Radar modeling; Through the wall; Through-the-wall radars; Ultra wideband radars; Coherent distributed radar; hybrid distributed radar modeling; impulse radio ultrawideband (IR-UWB) radar; through-the-wall radar